Urinary estrogen in the menstrual cycle - Salinas Hurtado, José (1969)
The method of Brown, based on adsorption chromatography on alumina columns , was applied to determine , for the first time in our environment , changes in the urinary excretion of estrone , 17B -estradiol and estriol, in a group of 8 normal women , between 18 and 38 years old, at three points in menstrual cycle : foliculor phase , ovulatory and luteal phase peak . The results agreed with those reported by several authors, using the same method or similar methods . Cyclic variations of three estrogen excretion give evidence of ovulation demonstrated in 6 cases ; in the remaining two could not be ruled out, although not definitively proven the possibility of anovulatory cycles . Estrogenic good correlation between variations and basal temperature curves and between estriol excretion and body weight was observed. In a case of testicular feminization , the dosages of estrogen correlated well with the degree of feminization clinically detectable with other laboratory and anatomic findings.